Massive Pulmonary Embolism Complicating Coronavirus Disease 2019 (COVID-19) Pneumonia: A Case Report - Shruti Hegde; Gemini Yesodharan; John Tedrow; Alena Goldman (Case Reports in Critical Care)
Background. Patients with severe COVID-19 pneumonia are hypercoagulable and are at risk for acute pulmonary embolism. Timely diagnosis is imperative for their prognosis and recovery. This case describes an otherwise healthy 55-year-old man with respiratory failure requiring mechanical ventilatory support secondary to COVID-19 pneumonia. Massive acute pulmonary embolism with right heart failure complicated his course. Case. A healthy 55-year-old man presented to our emergency department (ED) with a sore throat, cough, and myalgia. A nasopharyngeal swab was obtained, and he was discharged for home quarantine. His swab turned positive for SARS-CoV-2 infection on real-time reverse transcriptase-polymerase chain reaction assay (RT-PCR) on day 2 of his ED visit. A week later, he represented with worsening shortness of breath, requiring intubation for hypoxic respiratory failure due to COVID-19 pneumonia. Initially, he was easy to oxygenate, had no hemodynamic compromise, and was afebrile. On day 3, he became febrile and developed significant hemodynamic instability requiring maximum vasopressor support and oxygenation difficulty. His ECG revealed sinus tachycardia with S1Q3T3 pattern. On bedside TTE, there was evidence of right heart strain and elevated pulmonary artery systolic pressure of 45 mmHg. All data was indicative of a massive APE as the etiology for his hemodynamic collapse. A decision was made to forgo computed tomography pulmonary angiography (CTPA), given his clinical instability, and systemic thrombolytic therapy was administered. Within the next 12-24 hours, his hemodynamic status significantly improved. Conclusions. This case highlights the importance of considering massive APE in COVID-19 patients as a cause of the sudden and rapid hemodynamic decline. Furthermore, timely diagnosis can be made to aid in appropriate management with the help of bedside TTE and ECG in cases where CTPA is not feasible secondary to the patient’s hemodynamic instability.